ANALISIS JAM KERJA ANAK DI SUMATERA BARAT - Selli Nelonda (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2014)
Abstract : As in other countries, in Indonesia, children are considered very valuable both as themselves as well as human resources that will determine the future of the country. For various reasons, there are still quite a lot of children in Indonesia, especially in West Sumatra are leaving school and entering the labor market too early. This in turn will lead to low levels of school enrollment. The low level of school participation is allegedly linked to the issue of child labor hours. Long working hours for children will lose the impact of educational opportunities, learning time is reduced even none at all. Using data Susenas West Sumatra 2012 and logistic regression showed that employment status variable RT head, sector head of household work (agriculture), the working hours of children, as well as the status of child labor (workers family / unpaid) significant partial affect the chances of child labor to school. While variables such as gender, region, education level of the head of household, type of work  RT, the proportion of food, as well as the age of the head of household is partially not affect the chance of working children aged 10-15 years to go to school Kata Kunci : logistic regression model, odds ratio, working children   Abstrak : Seperti halnya di negara lain, di Indonesia anak-anak dianggap sangat berharga baik sebagai diri mereka sendiri maupun sebagai sumber daya manusia yang akan menentukan masa depan negara. Untuk berbagai alasan, masih cukup banyak anak-anak di Indonesia khususnya Sumatera Barat yang meninggalkan sekolah dan memasuki pasar tenaga kerja terlalu dini. Hal ini nantinya akan berakibat kepada rendahnya tingkat partisipasi sekolah. Rendahnya tingkat partipasi sekolah ini diduga terkait dengan isu jam kerja anak. Jam kerja yang panjang bagi anak akan memberi dampak kehilangan kesempatan memperoleh pendidikan, waktu belajar berkurang bahkan tidak ada sama sekali. Dengan menggunakan data Susenas Sumatera Barat tahun 2012 dan regresi logistik penelitian ini memberikan hasil bahwa variabel status pekerjaan kepala RT, sektor pekerjaan kepala rumah tangga (sektor pertanian), jam kerja anak, serta status pekerjaan anak (pekerja keluarga/tidak dibayar) secara parsial signifikan mempengaruhi peluang pekerja anak untuk bersekolah. Sedangkan variabel seperti jenis kelamin, wilayah, tingkat pendidikan kepala RT, jenis pekerjaan kepla RT, proporsi makanan, serta umur kepala RT secara parsial tidak berpengaruh terhadap peluang pekerja anak usia 10-15 tahun untuk masuk ke sekolah. Kata Kunci : regresi logistik, odds ratio, pekerja anak